Analisis Perencanaan Pembelajaran IPA pada Materi Ekosistem Kelas XII SMK Negeri 4 Padang - sari, rona taula (Universitas Muhammadiyah Surakarta, 2016)
To improve and produce graduated students of SMK relevance with the needs of business and industry, which continues growing significantly, then the vocational curriculum should be designed and implemented Â the developing competence. Teachers are required to be able to produce learners who are extremely competent and ready to face lifes challenges with confidence and high self confidence through a process of meaningful learning that he personally experienced to be able to apply his knowledge in everyday life. Therefore, teachers should be able to design their own learning plan to be based on a curriculum that has been made by the government. Planning learning is an important part in the implementation of education at the school. One lesson plans to be prepared by the teachers is the Learning Implementation Plan (RPP).This type of research is descriptive quantitative research but generally is in the form of case studies. Data collection techniques used in relation to the learning plan in the form of Learning Implementation Plan (RPP) made by teachers in the value of using Instrument RPP (IPKG-1).Based on the results of research on science teaching in the classroom Planning XII-DKV in SMK N 4 Padang on subjects Ecosystem terms of format already referred to the Teacher Performance Assessment Instrument (IPKG-1). Learning materials and learning resources are the criteria are not good (1.00 to 1.99). Teacher Performance Assessment Instrument (IPKG-1) provide an assessment of achieving the expected unfavorable (2.00 to 2.99) for the indicator, learning activities, learning objectives, assessment of learning outcomes. Good enough category (3.00 to 3.49) for kompenen RPP in general, SK and KD, the allocation of time and learning methods. Identity RPP and KD can be implemented in one or more meetings were with the highest fourth in both categories.Â